Kalimat Berdiatesis Aktif - Pasif Pada Kumpulan Cerpen Dilarang Menyanyi di Kamar Mandi Karya Seno Gumira Ajidarma - Nur Suryanah; Masta Hutajulu (Risenologi, 2021)
This study discusses the use of active and passive diathesis sentences contained in the short story. This study aims to provide an overview of the use of active-passive diathesis sentences in the short story text. The method used in this study is a qualitative descriptive method with content analysis techniques of sentence variations. The object of this research uses the sentences contained in the book collection of short stories "Don't Sing in the Bathroom" by Seno Gumira Ajidarma. Based on the results of the study, it can be concluded that the use of sentences with active diathesis is more often used, namely 76.4% compared to sentences with passive diathesis, which is 23.6%